Multi-instrument mapping of the small-scale flow dynamics related to a cusp auroral transient - K. Oksavik; J. Moen; H. C. Carlson; R. A. Greenwald; S. E. Milan; M. Lester; W. F. Denig; R. J. Barnes (Annales Geophysicae, 2005)
In this paper we focus on flux transfer events (FTEs) and poleward moving auroral forms (PMAFs) in the cusp region, combining data from the EISCAT Svalbard radar, SuperDARN HF radars, ground-based optics, and three low-altitude polar-orbiting spacecraft. During an interval of southward interplanetary magnetic field the EISCAT Svalbard radar tracked a train of narrow flow channels drifting into the polar cap. One 30-60 km wide flow channel surrounded by flow running in the opposite direction is studied in great detail from when it formed equatorward of the cusp aurora, near magnetic noon, until it left the field-of-view and disappeared into the polar cap. Satellite data shows that the flow channel was on open field lines. The flow pattern is consistent with field-aligned currents on the sides of the flow channel; with a downward current on the equatorward side, and an upward current on the poleward side. The poleward edge of the flow channel was coincident with a PMAF that separated from the background cusp aurora and drifted into the polar cap. A passage of the DMSP F13 spacecraft confirms that the FTE flow channel was still discernable over 15 minutes after it formed, as the spacecraft revealed a 30–40 km wide region of sunward flow within the anti-sunward background convection. From the dimensions of the flow channel we estimate that the magnetic flux contained in the event was at least 1 MWb. This data set also shows that Birkeland current filaments often seen by low-altitude spacecraft in the cusp/mantle are really associated with individual FTE events or a train of FTEs in progress. As the region 0 or cusp/mantle current represents the statistical average consistent with the large-scale flow pattern, we therefore introduce a new term – FTE currents – to denote the unique pair of Birkeland current sheets that are associated with individual meso-scale FTE flow disturbances. The poleward moving auroral forms (PMAFs), often referred to in the literature, are the optical signature of the upward FTE current. ...